O Tribunal de Contas do estado da Paraíba e a avaliação da gestão educacional: indicadores de desempenho, análise e perspectivas - Costa Filho, João Alfredo Nunes da (2014)
This study reports a managerial view on developing the assessment processing of children and primary education in the municipality of Paraíba, from the perspective of States Court Account. The main objective was to check if the Court is examining correctly in results aspects of the process in educational programs in development of the study. It was found that the Court only observes two indicators: a) The percentage of tax proceeds transferred and invested in maintenance and development teaching; b) The percentage of resources from National Development Fund of Basic Education (FUNDEB) invested in teacher s remuneration. It was noticeable that these indicators were insufficient for supplying a general insight of the results of the educational system. That is why it was proposed to introduce six new indicators for complementing the assessment of performance measures currently used by the Court. These new indicators supply a view of the results to the community. It was observed that the Court already had a method for the analysis of this information It is Paraiba s System Indicators of Development from Public Expenditure (IDGPB). With the adoption of these new methods, the analysis carried out by Court overtook the financial aspects and passed to another area, such as: school infrastructure, teaching performance, school quality and access to education. This subject is essential for adapting the Court system controls to a new model in which focus passes from bureaucratic and formal to resolution and management. Besides the growth of analysis supplies to society a real diagnosis from the situation of the child and primary education in municipality of Paraíba State and assists managers in decision-making.